Laminate and packaging container

A two-layer laminate with ethylene-vinyl alcohol copolymer and a resin composition of unmodified polyolefin addresses plastic reduction and adhesive strength issues, ensuring gas barrier properties and content resistance in packaging materials.

JP2025009949APending Publication Date: 2025-01-20DAI NIPPON PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024101524
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-01-17
Filing Date
2024-06-24
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing laminates for packaging materials face challenges in reducing plastic usage, maintaining gas barrier properties, and ensuring content resistance while avoiding delamination due to issues with adhesive strength and resin decomposition, especially when exposed to various contents.

Method used

A laminate structure with a two-layer coextrusion of ethylene-vinyl alcohol copolymer and a resin composition containing unmodified polyolefin and maleic anhydride-modified polyolefin, where the unmodified polyolefin content is between 10% to 80% by mass, and the thickness of the adhesive resin layer is 3 μm to 20 μm, enhancing adhesion and heat resistance.

Benefits of technology

The laminate effectively reduces resin usage, maintains excellent gas barrier properties, improves processing suitability, and ensures content resistance, preventing delamination even with diverse contents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009949000001_ABST
    Figure 2025009949000001_ABST
Patent Text Reader

Abstract

To provide a laminate which enables manufacture of a packaging container that easily reduces a used amount of a resin in a barrier layer, is excellent in gas barrier property, improves working suitability, and is excellent in content resistance, and a packaging container using the same.SOLUTION: A laminate 10 includes at least a first layer 11 and a barrier layer 12, wherein the barrier layer 12 is two layers of co-extrusion layers of a gas barrier resin layer 14 and an adhesive resin layer 15, the gas barrier resin layer 14 is positioned between the first layer 11 and the adhesive resin layer 15, the gas barrier resin layer 14 contains an ethylene-vinyl alcohol copolymer, the adhesive resin layer 15 is composed of a resin composition containing unmodified polyolefin and maleic anhydride modified polyolefin, a content of the unmodified polyolefin in the adhesive resin layer 15 is 10 mass% or more and 40 mass% or less, and thickness of the adhesive resin layer 15 is 3 μm or more and 20 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate and a packaging container. [Background technology]

[0002] Conventionally, resin films made of resin materials have been used as constituent materials of packaging materials, and laminates for packaging materials made of a plurality of resin films have been widely used. Various functions are required of packaging materials depending on the contents to be filled. For example, gas barrier properties such as oxygen barrier properties and water vapor barrier properties are required to prevent deterioration of the contents over time.

[0003] Laminates for packaging materials with improved gas barrier properties using ethylene-vinyl alcohol copolymer (EVOH), a gas barrier resin, have been proposed. For example, Patent Document 1 describes a packaging material in which a base film, a barrier film, and a sealant film are laminated in this order, and the barrier film is a co-extruded film having a structure of an ethylene-vinyl alcohol copolymer layer / an adhesive resin layer / a polyolefin layer. This barrier packaging material has appropriate gas barrier properties and aroma retention. Patent Document 2 describes a laminate comprising a substrate and a barrier layer, the barrier layer being formed by co-extrusion of three types of five layers: polyolefin resin / adhesive resin / ethylene-vinyl alcohol copolymer / adhesive resin / polyolefin resin. This laminate can be widely used for packaging materials that require barrier properties or packaging materials that have quality requirements for high resistance. Furthermore, Patent Document 3 describes a paper container for liquids that is composed of a laminate using a nylon film or an EVOH film as a barrier layer. This paper container for liquids can prevent a decrease in the adhesive strength of the adhesive layer used to bond the barrier layer and the sealant layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-304139 [Patent Document 2] JP 2012-76305 A [Patent Document 3] JP 2013-144556 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, in order to reduce the environmental load, such as reducing carbon dioxide emissions, there has been a strong demand for reducing the amount of plastic used in laminates that constitute packaging materials. Furthermore, there is also the advantage that reducing the amount of plastic used leads to cost reduction. Therefore, instead of the three-kind, three-layer coextrusion described in Patent Document 1 or the three-kind, five-layer coextrusion described in Patent Document 2, it is required to produce a film by two-kind, two-layer coextrusion to reduce the number of layers and the amount of resin.

[0006] The coextrusion layers described in Patent Documents 1 and 2 are formed by coextrusion of three types of resins, namely, an ethylene-vinyl alcohol copolymer, an adhesive resin, and a polyolefin resin. When polyolefin is excluded from these three types of resins and a two-layer film is formed by coextrusion using only an ethylene-vinyl alcohol copolymer and an adhesive resin, the following problems arise.

[0007] Maleic anhydride-modified polyolefins have been used as adhesive resins. Maleic anhydride-modified polyolefins are resins in which the adhesive component maleic anhydride is graft-polymerized onto a polyolefin, resulting in higher adhesion to an ethylene-vinyl alcohol copolymer layer than unmodified polyolefins. Maleic anhydride-modified polyolefins contain an excess of the adhesive component maleic anhydride, and therefore tend to adhere to metal chill rolls or rubber nip rolls used in the process of producing laminates. When a film is produced by co-extrusion of two layers of ethylene-vinyl alcohol copolymer and maleic anhydride-modified polyolefin, the layer of maleic anhydride-modified polyolefin that constitutes one side of the produced film adheres to a metal chill roll or a rubber nip roll, making it difficult to remove the film from the metal chill roll or the rubber nip roll, and thus making it difficult to process the film into a laminate.

[0008] Ethylene-vinyl alcohol copolymers and adhesive resins may change color or emit odors or foreign matter due to decomposition at high temperatures, but unmodified polyolefins are less likely to suffer from such phenomena. For this reason, unmodified polyolefins can be said to be resins with relatively excellent heat resistance. In the co-extrusion of three resins described in Patent Documents 1 and 2, unmodified polyolefins with excellent heat resistance are extruded at high temperatures, and the entire co-extruded layer is heated to a high temperature, causing the layers to melt together and increasing the adhesive strength between the layers. When unmodified polyolefin is excluded from the three resins used for coextrusion and a two-layer film is produced by coextrusion of an ethylene-vinyl alcohol copolymer and an adhesive resin, the absence of unmodified polyolefin with excellent heat resistance in the coextruded layer makes it difficult to maintain the entire coextruded layer at a high temperature, and the coextruded layers are less likely to fuse together, which leads to a decrease in adhesive strength. As a result, there are problems such as delamination occurring easily and a decrease in gas barrier properties.

[0009] Also, instead of using an ethylene-vinyl alcohol copolymer, a gas barrier layer such as a silica-deposited polyethylene terephthalate film, an alumina-deposited polyethylene terephthalate film, or an aluminum foil is laminated to improve the gas barrier properties of the laminate. However, in packaging containers made from laminates having such a gas barrier layer, delamination may occur in the laminate depending on the contents filled therein. For example, when a silica-deposited polyethylene terephthalate film or an alumina-deposited polyethylene terephthalate film is used for a packaging container filled with an alkaline content, the polyethylene terephthalate is hydrolyzed by the alkali, and delamination may occur in the laminate. Also, when an aluminum foil is used for a packaging container filled with an acidic content, the aluminum foil is corroded by the acid, and delamination may occur in the laminate. Furthermore, when a solvent is filled as the content in a packaging container, the adhesive used in the laminate is dissolved by the solvent, and delamination may occur in the laminate. Therefore, there has been a demand for a packaging container having excellent content resistance suitable for use with a variety of contents, and a laminate from which such a packaging container can be produced.

[0010] Therefore, an object of the present disclosure is to provide a laminate that can be used to produce a packaging container that can easily reduce the amount of resin used in the barrier layer, has excellent gas barrier properties, has improved processability, and is excellent in content resistance. Another object of the present disclosure is to provide a packaging container using the laminate. [Means for solving the problem]

[0011] The present inventors have discovered that the above problems can be solved by forming a single layer from a resin composition in which an adhesive resin and an unmodified polyolefin are mixed, instead of forming a layer of an adhesive resin and a layer of an unmodified polyolefin as separate layers. In a resin composition obtained by mixing an adhesive resin with an unmodified polyolefin, the adhesiveness is appropriately reduced compared to the adhesive resin before being mixed with the unmodified polyolefin, and adhesion to a metal chill roll or a rubber nip roll is suppressed, thereby improving processability. Furthermore, by co-extruding the resin composition with an ethylene-vinyl alcohol copolymer at a certain thickness or more, a certain amount of heat is stored in the resin composition, making it easier to maintain the entire co-extruded layer at a high temperature, and the layers are sufficiently fused together. Even if the adhesiveness of the resin composition is reduced, the interlayer adhesive strength of the laminate is less likely to decrease, and as a result, the gas barrier properties are less likely to decrease. Furthermore, by using an ethylene-vinyl alcohol copolymer as a laminate instead of a gas barrier layer such as a silica-vapor-deposited polyethylene terephthalate film, an alumina-vapor-deposited polyethylene terephthalate film, or an aluminum foil, a packaging container produced using the laminate has excellent content resistance. The present disclosure has been completed based on these findings and through further investigation.

[0012] The present disclosure is solved by the following embodiments. <1> A laminate comprising at least a first layer and a barrier layer, the barrier layer is a co-extruded layer of two layers, a gas barrier resin layer and an adhesive resin layer, the gas barrier resin layer is located between the first layer and the adhesive resin layer, the gas barrier resin layer contains an ethylene-vinyl alcohol copolymer, the adhesive resin layer is made of a resin composition containing an unmodified polyolefin and a maleic anhydride-modified polyolefin, The content of the unmodified polyolefin in the adhesive resin layer is 10% by mass or more and 80% by mass or less, The thickness of the adhesive resin layer is 3 μm or more and 20 μm or less. <2> The content of groups derived from maleic anhydride in the adhesive resin layer is 0.18% by mass or more and 0.25% by mass or less. <1> The laminate according to claim 1. <3> The melt flow rate of the resin composition is 2 g / 10 min or more and 13 g / 10 min or less. <1> or <2> The laminate according to claim 1. <4> The thickness of the gas barrier resin layer is 3 μm to 20 μm. <1> ~ <3> 13. The laminate according to claim 12 . <5> In the ethylene-vinyl alcohol copolymer, the content of structural units derived from ethylene is 20 mol% or more and 60 mol% or less. <1> ~ <4> 13. The laminate according to claim 12 . <6> The melt flow rate of the ethylene-vinyl alcohol copolymer is 0.1 g / 10 min or more and 15 g / 10 min or less. <1> ~ <5> 13. The laminate according to claim 12 . <7> The thickness of the barrier layer is 10 μm or more and 30 μm or less. <1> ~ <6> 13. The laminate according to claim 12 . <8> A second layer is further provided on the adhesive resin layer. <1> ~ <7> 13. The laminate according to claim 12 . <9> The second layer is a sealant film. <8> The laminate according to claim 1. <10> the first layer comprising paper; <1> ~ <9> 13. The laminate according to claim 12 . <11> The oxygen permeability measured in accordance with JIS K 7126-2:2006 at a temperature of 23°C and a relative humidity of 60% is 10cc / m 2 ·day·atm or less, <1> ~ <10> 13. The laminate according to claim 12 . <12> <1> ~ <11> A packaging container comprising the laminate described in any one of the above. <13> A liquid paper container, <12> The packaging container according to claim 1. Effect of the Invention

[0013] The present disclosure can provide a laminate that can easily reduce the amount of resin used in the barrier layer, has excellent gas barrier properties, and can be used to produce a packaging container that has improved processability and excellent content resistance. The present disclosure can also provide a packaging container using the laminate. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present disclosure. [Diagram 3] FIG. 1 is a perspective view showing a standing pouch which is one embodiment of a packaging container according to the present disclosure. [Figure 4] FIG. 1 is a front view showing a pillow bag, which is one embodiment of a packaging container according to the present disclosure. [Diagram 5] 1 is a front view showing a three-sided sealed bag, which is one embodiment of a packaging container according to the present disclosure. [Figure 6] 1 is a front view showing a four-sided sealed bag, which is one embodiment of a packaging container according to the present disclosure. [Figure 7] 1 is a perspective view showing a Gabel-top type liquid paper container which is one embodiment of a packaging container according to the present disclosure. FIG. [Figure 8] FIG. 1 is a perspective view showing a flat-top type liquid paper container which is one embodiment of a packaging container according to the present disclosure. [Figure 9] FIG. 1 is a perspective view showing a brick-shaped liquid paper container, which is one embodiment of a packaging container according to the present disclosure. [Figure 10] 1 is a perspective view of a paper cup, which is one embodiment of a packaging container according to the present disclosure, with a portion cut away. [Figure 11] 1 is a partially cutaway front view of a paper cup, which is one embodiment of a packaging container according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Note that the present disclosure is not limited to the following embodiments. Furthermore, the components in the following embodiments include those that a person skilled in the art can easily imagine and those that are substantially the same. Furthermore, the components disclosed in the following embodiments can be appropriately combined.

[0016] 1, a laminate 10 of the present disclosure includes at least a first layer 11 and a barrier layer 12. The barrier layer 12 is a coextrusion layer of a gas barrier resin layer 14 and an adhesive resin layer 15. The gas barrier resin layer 14 is located between the first layer 11 and the adhesive resin layer 15.

[0017] In one embodiment of the present disclosure, the laminate 10 includes a first layer 11, a barrier layer 12, and a second layer 13, as shown in Fig. 2. The barrier layer 12 is a coextrusion layer of a gas barrier resin layer 14 and an adhesive resin layer 15. The gas barrier resin layer 14 is located between the first layer 11 and the adhesive resin layer 15. The adhesive resin layer 15 is located between the gas barrier resin layer 14 and the second layer 13. The laminate 10 shown in Fig. 2 further includes a second layer 13 on the adhesive resin layer 15 of the laminate 10 shown in Fig. 1.

[0018] In the laminate of the present disclosure, the oxygen permeability measured in accordance with JIS K 7126-2:2006 under an environment of a temperature of 23° C. and a relative humidity of 60% RH is preferably 10 cc / m 2 ·atm·day or less, and more preferably 5cc / m 2 ·atm·day or less, and more preferably 2cc / m 2 ·atm·day or less, and particularly preferably 1cc / m 2 When the oxygen permeability of the laminate satisfies the above numerical range, the laminate has suitable oxygen barrier properties, and therefore when used in a packaging container, adverse effects on the contents of the packaging container can be suppressed. The laminate of the present disclosure is preferably impermeable to oxygen. Therefore, the oxygen permeability of the laminate of the present disclosure is preferably 0 cc / m 2 ·atm·day is most preferable, but 0.01cc / m 2 Atm day or more is practical, and 0.05cc / m 2 Atm-day or more is more practical, and 0.1cc / m 2 It is more practical to have atm-day or more. The oxygen permeability of the laminate is measured using an oxygen permeability measuring device, specifically, by the method described in the Examples below.

[0019] Each layer constituting the laminate of the present disclosure will be described below.

[0020] [First layer] As the first layer, any resin film or sheet can be used depending on the application of the laminate. For example, when the laminate is applied to a refill pouch for sealing and packaging refillable shampoo or rinse, the first layer is preferably excellent in mechanical strength such as tensile strength, flexural strength, and impact strength, as well as printability. For example, as the first layer, a nylon film, a polyester film such as a polyethylene terephthalate film or a polybutylene terephthalate film, or a polyolefin film such as a polypropylene film or a polyethylene film can be suitably used. These films may be unstretched films, uniaxially stretched films, or biaxially stretched films. They may also be vapor-deposited films in which a metal such as aluminum or an inorganic oxide such as aluminum oxide or silicon oxide is vapor-deposited on these films. Alternatively, any paper can be used as the first layer. For example, known papers such as fine paper, imitation paper, art paper, coated paper, pure white roll paper, kraft paper, label paper with improved water resistance, cup base paper, card paper, ivory paper, paperboard such as manila cardboard, milk carton base paper, cup base paper, synthetic paper, clay-coated paper, etc. can be used. When the first layer is paper, the packaging container using the laminate of the present disclosure, coupled with the fact that the amount of resin used in the barrier layer can be easily reduced, makes it easier to obtain a paper mark for paper container packaging based on the Resource Effective Utilization Promotion Law (Law Concerning the Promotion of Effective Utilization of Resources). Alternatively, a metal foil obtained by rolling a metal can also be used as the first layer. As the metal foil, a conventionally known metal foil can be used. From the viewpoints of gas barrier properties that prevent the transmission of oxygen gas, water vapor, etc., and light blocking properties that prevent the transmission of visible light, ultraviolet light, etc., aluminum foil is preferred. These films, sheets, papers, or metal foils may be used alone or in combination. For example, a laminated paper may be used in which an anchor coat layer described below is formed on one side of a paper and a resin is extruded onto the anchor coat layer to form a laminate. In order to improve the ease of opening, the first layer may be subjected to SC processing, laser processing, sewing machine processing or slit processing.

[0021] [Print layer] The laminate of the present disclosure may include a printed layer. The printed layer is a layer on which any desired printed pattern such as letters, numbers, pictures, figures, symbols, designs, etc. is formed for decoration, indication of contents, indication of expiration date, indication of manufacturer, indication of seller, imparting aesthetic feeling, etc. When the laminate of the present disclosure includes a printed layer, the printed layer is preferably formed on either one surface of the first layer.

[0022] [Anchor coat layer] In one embodiment, the laminate of the present disclosure may further include an anchor coat layer on the first layer or on the surface of the first layer on which the printed layer is formed. This can improve the interlayer adhesion between the first layer and the gas barrier resin layer. The anchor coat layer is formed from an anchor coating agent.

[0023] Examples of the anchor coating agent include polyurethane-based, polyolefin-based, and epoxy resin-based anchor coating agents. In one embodiment, the anchor coating agent is a two-component curing resin, and is composed of, for example, a polyol as a base agent and a polyisocyanate as a curing agent.

[0024] Examples of polyols include polyether polyols, polyester polyols, and Examples of the polyisocyanate include aromatic polyisocyanates such as tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, and polymethylene polyphenylene polyisocyanate, and aliphatic polyisocyanates such as hexamethylene diisocyanate and isophorone diisocyanate.

[0025] In one embodiment, the anchor coat layer is made of polyurethane obtained by reacting a polyol with a polyisocyanate. Specific examples of the polyurethane include polyether polyurethane, polyester polyurethane, and poly(meth)acrylic polyurethane.

[0026] The anchor coat layer can be formed, for example, by applying an anchor coat agent onto the first layer or onto the surface of the first layer on which the printed layer is formed. The anchor coat agent can be applied, for example, by a coating method such as a roll coating method, a gravure roll coating method, or a kiss coating method, or by a printing method.

[0027] The dry coating amount of the anchor coating agent is, for example, 0.01 g / m 2 More than 1g / m 2 Less than 0.03 g / m 2 More than 0.5g / m 2 Less than or equal to 0.05 g / m 2 More than 0.4g / m 2 The following is the result.

[0028] The thickness of the anchor coat layer is, for example, 0.05 μm or more and 3.0 μm or less, preferably 0.1 μm or more and 2.0 μm or less, and more preferably 0.2 μm or more and 1.0 μm or less.

[0029] [Gas barrier resin layer] The gas barrier resin layer contains an ethylene-vinyl alcohol copolymer as a gas barrier resin, which can improve the gas barrier properties of the laminate and can provide a laminate body that can be used to produce a packaging container with excellent content resistance.

[0030] In the ethylene-vinyl alcohol copolymer, the content of structural units derived from ethylene (hereinafter referred to as "ethylene content") is preferably 20 mol% or more, more preferably 25 mol% or more, and even more preferably 32 mol% or more, which can improve the processability of the laminate. Furthermore, the ethylene content of the ethylene-vinyl alcohol copolymer is preferably 60 mol % or less, more preferably 48 mol % or less, and even more preferably 44 mol % or less, which can improve the gas barrier properties of the laminate. The ethylene content of the ethylene-vinyl alcohol copolymer is a value measured by the NMR method.

[0031] The melting point (Tm) of the ethylene-vinyl alcohol copolymer is preferably 130°C or more and 200°C or less, more preferably 140°C or more and 195°C or less, and further preferably 150°C or more and 190°C or less.

[0032] From the viewpoint of processability, the melt flow rate (MFR) of the ethylene-vinyl alcohol copolymer is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, further preferably 0.5 g / 10 min or more, and particularly preferably 1 g / 10 min or more. Moreover, from the viewpoint of easily producing a laminate having a good appearance, the melt flow rate of the ethylene-vinyl alcohol copolymer is preferably 15 g / 10 min or less, more preferably 10 g / 10 min or less, even more preferably 5 g / 10 min or less, and particularly preferably 4 g / 10 min or less. The melt flow rate of the ethylene-vinyl alcohol copolymer is a value measured at a temperature of 190°C and a load of 2.16 kg in accordance with JIS K7210-1:2014. However, when the melting point of the ethylene-vinyl alcohol copolymer exceeds 190°C, the value is measured at a temperature of 210°C.

[0033] The content of the ethylene-vinyl alcohol copolymer in the gas barrier resin layer is, for example, 50% by mass or more, preferably 75% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, and particularly preferably 90% by mass or more, thereby improving the gas barrier property of the laminate.

[0034] The gas barrier resin layer may further contain a gas barrier resin other than the ethylene-vinyl alcohol copolymer, for example, at least one selected from polyamide, polyvinyl alcohol, polyacrylonitrile, polyester, polyurethane, and (meth)acrylic resin.

[0035] The gas barrier resin layer may contain various additives within the range that does not impair the properties of the layer, such as antioxidants, slip agents, plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducers, release agents, ion exchange agents, antiblocking agents, and color pigments.

[0036] The thickness of the gas barrier resin layer is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 8 μm or more. This can improve the gas barrier properties of the laminate. The thickness of the gas barrier resin layer is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. This can reduce the amount of resin used in the barrier layer. It has been conventional to improve the gas barrier properties of a laminate by laminating an ethylene-vinyl alcohol copolymer film. However, compared with the thickness of a gas barrier resin layer that can be formed by extrusion of an ethylene-vinyl alcohol copolymer, the thickness of a conventional ethylene-vinyl alcohol copolymer film is large, and there is a problem that it is difficult to process into a packaging container such as a liquid paper container. In the present disclosure, the gas barrier resin layer is a certain thickness or less, so that the suitability for processing into a packaging container is excellent.

[0037] [Adhesive resin layer] The adhesive resin layer is composed of a resin composition containing an unmodified polyolefin and a maleic anhydride modified polyolefin. Unmodified polyolefins are polyolefins that have not been modified, and examples of such polyolefins include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and polypropylene (PP). Maleic anhydride modified polyolefin is a resin in which maleic anhydride is graft-polymerized onto the main chain of polyolefin. Polyolefins that can be modified with maleic anhydride include high-density polyethylene (HDPE), medium-density polyethylene (MDPE), and low-density polyethylene (LDPE). (LDPE), linear low density polyethylene (LLDPE), and polypropylene (PP).

[0038] The resin composition may contain two or more kinds of unmodified polyolefins. For example, the resin composition may contain an unmodified low-density polyethylene and an unmodified linear low-density polyethylene. The resin composition may contain two or more kinds of maleic anhydride-modified polyolefins. For example, the resin composition may contain a low-density polyethylene modified with maleic anhydride and a linear low-density polyethylene modified with maleic anhydride.

[0039] The content of unmodified polyolefin in the adhesive resin layer (total content when the resin composition constituting the adhesive resin layer contains two or more unmodified polyolefins) is 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. The content of unmodified polyolefin in the adhesive resin layer (total content when the resin composition constituting the adhesive resin layer contains two or more unmodified polyolefins) is 80% by mass or less, preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The content of maleic anhydride-modified polyolefin in the adhesive resin layer (total content when the resin composition constituting the adhesive resin layer contains two or more types of maleic anhydride-modified polyolefin) is preferably 20% by mass or more, more preferably 40% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more. The content of maleic anhydride-modified polyolefin in the adhesive resin layer (total content when the resin composition constituting the adhesive resin layer contains two or more types of maleic anhydride-modified polyolefin) is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 75% by mass or less.

[0040] In the conventional technology, maleic anhydride-modified polyolefins have been used alone in the adhesive resin layer. However, commercially available maleic anhydride-modified polyolefins have an excessive amount of maleic anhydride, which is an adhesive component, grafted onto the polyolefin, and therefore tend to adhere to a metal chill roll or a rubber nip roll used in the process of producing a laminate. On the other hand, when an unmodified polyolefin is used alone instead of a maleic anhydride-modified polyolefin, the adhesive component maleic anhydride is not present in the unmodified polyolefin, so that the adhesive strength between the adhesive resin layer and the second layer or the adhesive strength between the adhesive resin layer and the gas barrier resin layer decreases, making the laminate more susceptible to interlayer delamination and reducing the gas barrier properties. In the present disclosure, the resin composition constituting the adhesive resin layer contains a certain proportion of unmodified polyolefin that does not contain an adhesive component, in addition to maleic anhydride modified polyolefin that contains an adhesive component, so that the adhesive resin layer exhibits appropriate adhesion such that it is difficult to adhere to a metal chill roll or a rubber nip roll, but is easy to adhere to the second layer and the gas barrier resin layer, thereby achieving both excellent gas barrier properties and improved processability.

[0041] The content of unmodified polyolefin and the content of maleic anhydride modified polyolefin in the adhesive resin layer can be analyzed from peaks detected by, for example, differential scanning calorimetry (DSC), infrared spectroscopy (IR), or nuclear magnetic resonance (NMR).

[0042] Since the resin composition constituting the adhesive resin layer contains unmodified polyolefin in addition to maleic anhydride-modified polyolefin, the content of groups derived from maleic anhydride in the adhesive resin layer is smaller than that of an adhesive resin layer formed from a commercially available maleic anhydride-modified polyolefin. In the present disclosure, the content of groups derived from maleic anhydride in the adhesive resin layer is preferably 0.29% by mass or less, more preferably 0.25% by mass or less, and even more preferably 0.23% by mass or less. This makes it difficult for the adhesive resin layer to adhere to a metal chill roll or a rubber nip roll during the process of manufacturing the laminate. In addition, the content of groups derived from maleic anhydride in the adhesive resin layer is preferably 0.1% by mass or more, more preferably 0.15% by mass or more, and even more preferably 0.2% by mass or more. This makes it easier for the adhesive resin layer to adhere to the second layer and the gas barrier resin layer, and prevents delamination of the laminate. The content of the group derived from maleic anhydride in the adhesive resin layer is the ratio of the mass of the group derived from maleic anhydride (-C4H3O3) to the mass of all components constituting the adhesive resin layer. The content of the group derived from maleic anhydride in the adhesive resin layer is measured by infrared absorption spectroscopy, specifically, by the method described in the Examples below.

[0043] From the viewpoint of processability, the melt flow rate of the resin composition is preferably 2 g / 10 min or more, more preferably 5 g / 10 min or more, and even more preferably 6 g / 10 min or more. Further, from the viewpoint of facilitating the production of a laminate having a good appearance, the melt flow rate of the resin composition is preferably 13 g / 10 min or less, more preferably 10 g / 10 min or less, and even more preferably 7 g / 10 min or less. The melt flow rate of the resin composition is a value measured in accordance with JIS K7210-1:2014 under conditions of a temperature of 190°C and a load of 2.16 kg.

[0044] The resin composition may further contain other resins in addition to the unmodified polyolefin and the maleic anhydride-modified polyolefin, for example, at least one selected from polyolefins modified with substances other than maleic anhydride (e.g., maleic acid, fumaric acid, esters, or metal salts), vinyl resins, polyethers, polyesters, polyamides, polyurethanes, silicone resins, epoxy resins, and phenolic resins.

[0045] The resin composition may contain various additives within the range that does not impair the properties, such as antioxidants, slip agents, plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducers, release agents, ion exchange agents, antiblocking agents, and color pigments.

[0046] The thickness of the adhesive resin layer is 3 μm or more, preferably 6 μm or more, and more preferably 9 μm or more. This makes it easier to heat the entire coextrusion layer to a high temperature when extruding the resin composition in the process of producing the laminate. As a result, the layers are sufficiently melted together, and the adhesive strength between the layers of the produced laminate can be maintained. In addition, the thickness of the adhesive resin layer is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. This makes it possible to reduce the amount of resin used in the barrier layer.

[0047] [Barrier layer] The barrier layer is a coextrusion layer of two layers, a gas barrier resin layer and an adhesive resin layer. The coextrusion layer is a layer formed by a coextrusion method. Unlike the dry lamination method in which simple single films are bonded together, the film formation by the co-extrusion method is carried out by extruding multiple molten resins through multiple thin slit-like gaps. Therefore, the interface between layers formed by the co-extrusion method shows a very unique structure. This structure is significantly different from the interlayer structure caused by entanglement interactions such as self-adhesion in the dry lamination method. Specifically, the interface between layers formed by the co-extrusion method forms an interlocking structure in which the crystals of each resin penetrate each other, and has a very complex structure.

[0048] The barrier layer can be formed, for example, by co-extruding the resin constituting the gas barrier resin layer and the resin composition constituting the adhesive resin layer. More specifically, the barrier layer can be produced by simultaneously extruding two layers, an ethylene-vinyl alcohol copolymer and an adhesive resin, onto the first layer using a co-extrusion molding device. This results in a laminate in which the barrier layer, which is a two-layer co-extrusion layer of the gas barrier resin layer and the adhesive resin layer, and the first layer are laminated together. Note that the barrier layer produced by the co-extrusion method is an unstretched layer.

[0049] From the viewpoint of obtaining a laminate having excellent gas barrier properties, the thickness of the barrier layer is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 16 μm or more. From the viewpoint of reducing the amount of resin used in the barrier layer, the thickness of the barrier layer is preferably 30 μm or less, more preferably 24 μm or less, and even more preferably 20 μm or less.

[0050] [Second layer] As the second layer, the same film, sheet or paper as the first layer can be used. The second layer is preferably a film having excellent heat sealability, i.e., a sealant film, which can be melted by heating or the like to perform heat sealing in which the second layers are fused together, and a packaging container can be easily produced from the laminate. Specific examples of heat seals include bar seals, rotary roll seals, belt seals, impulse seals, high frequency seals, and ultrasonic seals.

[0051] The second layer and the barrier layer can be bonded together by extrusion lamination (so-called sandwich lamination) via an adhesive layer. In this case, the adhesive layer can be made of a polyolefin-based heat-adhesive resin (e.g., LDPE), as well as a simple substance such as an ethylene-methacrylic acid copolymer, an ethylene-acrylic acid copolymer, or an ionomer, or a resin obtained by blending these with an adhesion improver such as a hard resin. Alternatively, a gas barrier resin layer and an adhesive resin layer may be co-extruded onto the first layer, and the first layer and the second layer may be laminated via the gas barrier resin layer and the adhesive resin layer, and bonded together by a co-extrusion method, which makes it possible to omit a dry laminate layer or an adhesive layer between the adhesive resin layer and the second layer, and thus reduces the amount of resin used.

[0052] The laminate according to the present disclosure may have an intermediate layer between the second layer and the barrier layer. Examples of the intermediate layer include a light-shielding layer and a strength-improving layer.

[0053] The second layer and the intermediate layer, and the intermediate layer and the barrier layer can be laminated by extrusion lamination, coextrusion or the like, in the same manner as in bonding the second layer and the barrier layer described above.

[0054] The layers constituting the first layer may be bonded to each other by dry lamination, or may be laminated by extrusion lamination, co-extrusion or the like as described above.

[0055] In either case, the adhesive strength between the layers can be increased by applying an anchor coating agent to the lamination surfaces beforehand or by subjecting them to a pretreatment such as a corona treatment.

[0056] [Packaging container] The laminate of the present disclosure can be suitably used for packaging containers. Examples of packaging containers include packaging bags, lids, laminate tubes, liquid containers, paper cups, various label materials, etc. Examples of packaging bags include packaging bags of various shapes such as standing pouch type, side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, joint seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, and gusset type. The thickness of the laminate can be appropriately determined depending on the application. For example, by reducing the thickness of the laminate, the stiffness of the laminate itself can be reduced, and the suitability for packaging machines such as bag making machines or filling machines can be improved. The thickness of the laminate is, for example, 30 μm or more and 300 μm or less, preferably 35 μm or more and 180 μm or less.

[0057] [Standing pouch] The application of the laminate of the present disclosure to a standing pouch will be described. FIG. 3 is a diagram showing a simplified example of the configuration of a standing pouch. As shown in FIG. 3, the standing pouch 30 is composed of two side sheets 31 and one bottom sheet 32. In the standing pouch 30, the side sheet 31 and the bottom sheet 32 ​​are composed of different members. The standing pouch 30 is a packaging bag formed by using a sealant film as the second layer of the laminate of the present disclosure constituting the side sheet 31, and making the sealant film into the innermost layer. In the present disclosure, the side sheet 31 and the bottom sheet 32 ​​of the standing pouch 30 are composed of different members, but this is not limited thereto, and the side sheet 31 and the bottom sheet 32 ​​may be composed of the same member. Furthermore, in the standing pouch 30, the side sheet 31 is formed using the laminate of the present disclosure, but the standing pouch of the present disclosure is not limited to this, and the bottom sheet 32 ​​may be formed using the laminate of the present disclosure, or both the side sheet 31 and the bottom sheet 32 ​​may be formed using the laminate of the present disclosure.

[0058] The standing pouch 30 can be suitably used as a packaging container for filling with liquid, for packaging chemical products, medicines, quasi-drugs, cosmetics, food, etc., for example, as an outer bag for a patch, or as a standing pouch used for refill contents such as liquid detergent, liquid fabric softener, liquid soap, etc.

[0059] [Pillow bags, three-sided sealed bags and four-sided sealed bags] Depending on the form of heat sealing the laminate, various packaging bags can be made in addition to a standing pouch. FIG. 4 is a diagram showing an example of a pillow bag, FIG. 5 is a diagram showing an example of a three-sided sealed bag, and FIG. 6 is a diagram showing an example of a four-sided sealed bag. In FIGS. 4 to 6, heat-sealed parts are indicated by hatching. The pillow bag 41 shown in FIG. 6 is obtained by using a sealant film as the second layer of the laminate, making a bag so that the sealant film is the innermost layer, and heat-sealing and bonding two opposing sides of the laminate. The three-sided sealed bag 42 shown in FIG. 7 is obtained by using a sealant film as the second layer of the laminate, making a bag so that the sealant film is the innermost layer, and heat-sealing and bonding three sides of the laminate. The four-sided sealed bag 43 shown in FIG. 8 is obtained by using a sealant film as the second layer of the laminate, making a bag so that the sealant film is the innermost layer, and heat-sealing and bonding four sides of the laminate.

[0060] [Liquid paper container] Next, a case where a liquid-storing paper container is formed using the laminate of the present disclosure will be described. Fig. 7 is a perspective view showing an example of a liquid-storing paper container 60. As shown in Fig. 7, the liquid-storing paper container 60 has a rectangular tubular body 61 including a side surface, a rectangular plate-shaped bottom 62, and an upper portion 63. The upper portion 63 has a pair of opposing inclined plates 63a and a pair of folded portions 64 that are located between the inclined plates 63a and are folded between the inclined plates 63a. A margin 65 is provided at the upper end of each of the pair of inclined plates 63a, and the pair of inclined plates 63a are bonded to each other by the margin 65 provided at the upper end of each of the pair of inclined plates 63a. A spout may be attached to one of the pair of inclined plates 63a, and the spout may be sealed with a cap.

[0061] The liquid paper container 60 employs paper or laminated paper as the first layer of the laminate of the present disclosure, and can be manufactured using the laminate by a conventionally known method. For example, the laminate can be made into a box to manufacture liquid paper containers 60 of various shapes, such as a gabled top type with a gable roof at the top, a flat top type with a flat top and a spout plug, and a brick type with a flat top and a rectangular brick shape with a straw hole. An example of a gable-top type liquid paper container is a liquid paper container 60 having a gable-top top 63 as shown in FIG. An example of a flat-top liquid-storing paper container is a liquid-storing paper container 60 having a flat top 63 and equipped with a spout plug 66, as shown in FIG. An example of a brick-shaped liquid paper container is a liquid paper container 60 having a flat top 63 and a straw hole 67, as shown in FIG.

[0062] The liquid paper container 60 can be suitably used as a packaging paper container for all types of liquids, including alcoholic beverages such as sake, shochu, and wine, dairy drinks such as milk, soft drinks such as orange juice and tea, and chemical products such as car wax, shampoo, and detergent.

[0063] [Paper cups] Next, a paper cup formed using the laminate of the present disclosure will be described. Fig. 10 is a perspective view of a paper cup with a part cut away. As shown in Fig. 10, paper cup 70 has a flange 71 at the top, a cylindrical body 72 with a diameter gradually increasing toward the opening, and a bottom 73 provided at the lower end (one end) of body 72. Body 72 has flange 71 with its upper end rounded outward. After the contents are placed in paper cup 70, it may be sealed by attaching a lid (not shown) along flange 71 of body 72. It is preferable that the lid has gas barrier properties. The paper cup 70 can be manufactured by a conventionally known method by employing paper or laminated paper as the first layer of the laminate of the present disclosure and using the laminate for the body 72. However, the paper cup of the present disclosure is not limited to this, and the bottom 73 may be formed using the laminate of the present disclosure, or both the body 72 and the bottom 73 may be formed using the laminate of the present disclosure.

[0064] Furthermore, the paper cup 70 may have an exterior body 74 on the outer periphery of the body 72, as shown in Fig. 11. The exterior body 74 may be, for example, paper. The body 72 is formed with a protrusion 75. The protrusion 75 is formed to provide a gap 76 for an air layer between the body 72 and the exterior body 74. One or more protrusions 75 are provided in the horizontal direction, and for example, two protrusions can be provided as shown in Fig. 11. EXAMPLES

[0065] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.

[0066] The various raw materials used in the laminates of the following Examples 1 to 19 and Comparative Examples 1 to 6 are as follows. Gas barrier resin A Ethylene-vinyl alcohol copolymer, product name: F171B, manufactured by Kuraray Co., Ltd., ethylene content: 32 mol%, melt flow rate: 1.7 g / 10 min (melt flow rate is a value measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) Gas barrier resin B Ethylene-vinyl alcohol copolymer, product name: F104B, manufactured by Kuraray Co., Ltd., ethylene content: 32 mol%, melt flow rate: 4.4 g / 10 min (melt flow rate is a value measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) Gas barrier resin C Ethylene-vinyl alcohol copolymer, product name: E173B, manufactured by Kuraray Co., Ltd., ethylene content: 44 mol%, melt flow rate: 2.5 g / 10 min (melt flow rate is a value measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) Gas barrier resin D Ethylene-vinyl alcohol copolymer, product name: DC3212B, manufactured by Mitsubishi Chemical Corporation, ethylene content: 32 mol%, melt flow rate: 12 g / 10 min (melt flow rate is a value measured in accordance with JIS K7210-1:2014 at a temperature of 210°C and a load of 2.16 kg) ·Adhesive resin A A resin composition obtained by mixing 60% by mass of linear low-density polyethylene modified with maleic anhydride (product name: NE827, manufactured by Mitsui Chemicals, Inc.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 5.6 g / 10 min) and 40% by mass of unmodified low-density polyethylene (product name: CE4009, manufactured by Sumitomo Chemical Co., Ltd.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 7.0 g / 10 min). Melt flow rate of adhesive resin A: 6.2 g / 10 min (Melt flow rate is measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) ·Adhesive resin B A resin composition obtained by mixing 20% ​​by mass of low-density polyethylene modified with maleic anhydride (product name: 40E710, manufactured by Dow Chemical Japan Co., Ltd.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 2.5 g / 10 min) and 80% by mass of unmodified low-density polyethylene (product name: CE4009, manufactured by Sumitomo Chemical Co., Ltd.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 7.0 g / 10 min). Melt flow rate of adhesive resin B: 6.1 g / 10 min (Melt flow rate is measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) ·Adhesive resin C A resin composition obtained by mixing 75% by mass of maleic anhydride-modified polypropylene (product name: QE840, manufactured by Mitsui Chemicals, Inc.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 8 g / 10 min) and 25% by mass of unmodified polypropylene (product name: F329RA, manufactured by Prime Polymer Co., Ltd.; melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 27 g / 10 min). Melt flow rate of adhesive resin C: 12.8 g / 10 min (Melt flow rate is measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg) ·Adhesive resin D Linear low-density polyethylene modified with maleic anhydride (product name: NE827, manufactured by Mitsui Chemicals, Inc., melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 5.6 g / 10 min) ·Adhesive resin E Ethylene-methacrylic acid copolymer (product name: N1108C, manufactured by Dow Mitsui Polychemicals Co., Ltd., melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 10 g / 10 min) Low density polyethylene A Product name: CE4009, manufactured by Sumitomo Chemical Co., Ltd., Melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 7.0 g / 10 min Low density polyethylene B Product name: Novatec LD LC520, manufactured by Japan Polyethylene Co., Ltd., melt flow rate measured in accordance with JIS K7210-1:2014 at a temperature of 190°C and a load of 2.16 kg: 3.6 g / 10 min.

[0067] [Example 1] A urethane anchor coating agent was applied at 0.4 g / m2 to one side of the biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd., thickness: 25 μm) which was the first layer. 2 The coating was applied in a dry coating amount of 1000 g / m to form an anchor coat layer. Onto the anchor coat layer, gas barrier resin A and adhesive resin A were co-extruded using a co-extruder, while a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 20 μm) was laminated as a second layer via the gas barrier resin A and adhesive resin A. At that time, the thickness of the gas barrier resin layer made of gas barrier resin A was set to 10 μm, and the thickness of the adhesive resin layer made of adhesive resin A was set to 10 μm. In this manner, a laminate of Example 1 was obtained in which the first layer, anchor coat layer, gas barrier resin layer, adhesive resin layer, and second layer were laminated in this order.

[0068] [Example 2] A laminate of Example 2 was obtained in the same manner as in Example 1, except that the thickness of the gas barrier resin layer was adjusted to 5 μm.

[0069] [Example 3] A laminate of Example 3 was obtained in the same manner as in Example 1, except that the thickness of the gas barrier resin layer was adjusted to 8 μm and the thickness of the adhesive resin layer was adjusted to 8 μm.

[0070] [Example 4] A laminate of Example 4 was obtained in the same manner as in Example 1, except that the thickness of the gas barrier resin layer was adjusted to 15 μm and the thickness of the adhesive resin layer was adjusted to 15 μm.

[0071] [Example 5] A laminate of Example 5 was obtained in the same manner as in Example 2, except that an unstretched polypropylene film (product name: FCMN, manufactured by Futamura Chemical Co., Ltd., thickness: 20 μm) was used as the second layer instead of the polyethylene film.

[0072] [Example 6] A laminate of Example 6 was obtained in the same manner as in Example 1, except that an unstretched polypropylene film (product name: FCMN, manufactured by Futamura Chemical Co., Ltd., thickness: 20 μm) was used as the second layer instead of the polyethylene film.

[0073] [Example 7] The laminate of Example 7 was obtained in the same manner as in Example 1, except that a 12 μm-thick biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd.) was used as the first layer instead of a 25 μm-thick biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd.), and a polyethylene terephthalate film with an aluminum vapor deposition film (product name: 1012, manufactured by Toray Film Processing Co., Ltd., thickness: 12 μm) was used as the second layer instead of the polyethylene film.

[0074] [Example 8] A laminate of Example 8 was obtained in the same manner as in Example 1, except that gas barrier resin B was used instead of gas barrier resin A as the gas barrier resin.

[0075] [Example 9] A laminate of Example 9 was obtained in the same manner as in Example 1, except that gas barrier resin C was used instead of gas barrier resin A as the gas barrier resin.

[0076] [Example 10] A laminate of Example 10 was obtained in the same manner as in Example 1, except that adhesive resin B was used instead of adhesive resin A as the adhesive resin.

[0077] [Example 11] A laminate of Example 11 was obtained in the same manner as in Example 6, except that adhesive resin C was used instead of adhesive resin A as the adhesive resin.

[0078] [Example 12] A laminate of Example 12 was obtained in the same manner as in Example 1, except that the second layer was not laminated and the gas barrier resin A and the adhesive resin A were simply co-extruded onto the anchor coat layer, in which the first layer, the anchor coat layer, the gas barrier resin layer, and the adhesive resin layer were laminated in that order.

[0079] [Example 13] A laminate of Example 13 was obtained in the same manner as in Example 1, except that gas barrier resin D was used instead of gas barrier resin A as the gas barrier resin.

[0080] [Example 14] Basis weight: 382g / m 2 A urethane anchor coating agent was applied to one side of the milk carton base paper at 0.4 g / m 2 The dry coating amount was 1000 μm to form an anchor coat layer. Low density polyethylene A was extruded onto the anchor coat layer with an extruder to a thickness of 25 μm. In this way, a first layer consisting of the milk carton base paper, the anchor coat layer, and the low density polyethylene layer was produced. The first layer of the milk carton base paper is coated with a urethane anchor coating agent at 0.4 g / m 2The coating was applied in a dry coating amount of 1000 μm to form an anchor coat layer. Onto the anchor coat layer, gas barrier resin A and adhesive resin A were co-extruded using a co-extruder, while a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 40 μm) was laminated as a second layer via the gas barrier resin A and adhesive resin A. At that time, the thickness of the gas barrier resin layer made of gas barrier resin A was set to 10 μm, and the thickness of the adhesive resin layer made of adhesive resin A was set to 10 μm. In this manner, a laminate of Example 14 was obtained in which the first layer, anchor coat layer, gas barrier resin layer, adhesive resin layer, and second layer were laminated in this order.

[0081] [Example 15] A laminate of Example 15 was obtained in the same manner as in Example 14, except that gas barrier resin B was used instead of gas barrier resin A as the gas barrier resin.

[0082] [Example 16] A laminate of Example 16 was obtained in the same manner as in Example 14, except that gas barrier resin C was used instead of gas barrier resin A as the gas barrier resin.

[0083] [Example 17] A laminate of Example 17 was obtained in the same manner as in Example 14, except that gas barrier resin D was used instead of gas barrier resin A as the gas barrier resin.

[0084] [Example 18] Basis weight: 382g / m 2 Instead of milk carton base paper, basis weight: 320g / m 2 A laminate of Example 18 was obtained in the same manner as in Example 17, except that the milk carton base paper was used.

[0085] [Example 19] Basis weight: 382g / m 2 Instead of milk carton base paper, basis weight: 400g / m 2A laminate of Example 19 was obtained in the same manner as in Example 17, except that the milk carton base paper was used.

[0086] [Example 20] A urethane anchor coating agent was applied at a rate of 0.4 g / m2 to the surface of a polyethylene terephthalate film (product name: IB-PET, manufactured by Dai Nippon Printing Co., Ltd., thickness: 12 μm) on which a vapor deposition film made of silicon oxide had been formed. 2 The coating was applied in a dry coating amount of 1000 μm to form an anchor coat layer. On the anchor coat layer, gas barrier resin A and adhesive resin A were co-extruded using a co-extruder, while a polyethylene film (trade name: M2005, manufactured by Aicello Co., Ltd., thickness: 40 μm) was laminated as a second layer through the gas barrier resin A and adhesive resin A to produce a laminate. At that time, the thickness of the gas barrier resin layer made of gas barrier resin A was set to 10 μm, and the thickness of the adhesive resin layer made of adhesive resin A was set to 10 μm. Hereinafter, this laminate is referred to as laminate A. Next, milk carton base paper (manufactured by Clearwater Paper Corporation, basis weight: 382 g / m 2 ) on one side of the sheet, apply 0.1 g / m of polyethyleneimine anchor coating agent. 2 The low-density polyethylene A was then extruded onto the anchor coat layer using an extruder to a thickness of 25 μm to prepare a laminate. Hereinafter, this laminate is referred to as laminate B. A polyethyleneimine anchor coating agent was applied at 0.1 g / m2 to the milk carton base paper surface of laminate B. 2 Onto the anchor coat layer, adhesive resin C was extruded to a thickness of 20 μm using an extruder, and the layer was laminated to the vapor-deposited film surface of laminate A with adhesive resin C interposed therebetween. In this way, a laminate of Example 20 was obtained in which the first layer, anchor coat layer, gas barrier resin layer, adhesive resin layer, and second layer were laminated in this order. The first layer in Example 20 was a laminate in which a low-density polyethylene layer, anchor coat layer, milk carton base paper, anchor coat layer, adhesive layer, and vapor-deposited film were laminated in this order.

[0087] [Example 21] A biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd., thickness: 12 μm) was applied with 3.0 g / m of a dry lamination adhesive on one side. 2 The urethane anchor coating agent was applied to the other surface of the biaxially oriented polyethylene terephthalate film at a dry coating amount of 0.4 g / m2 and then laminated to an aluminum foil (product name: 1N30, manufactured by Toyo Aluminum Co., Ltd., thickness: 7 μm). 2 A dry coating amount of 1000 g was applied to form an anchor coat layer. On the anchor coat layer, gas barrier resin A and adhesive resin A were co-extruded using a co-extruder, while a polyethylene film (trade name: M2005, manufactured by Aicello Co., Ltd., thickness: 40 μm) was laminated as a second layer through the gas barrier resin A and adhesive resin A to produce a laminate. At that time, the thickness of the gas barrier resin layer made of gas barrier resin A was set to 10 μm, and the thickness of the adhesive resin layer made of adhesive resin A was set to 10 μm. Hereinafter, this laminate is referred to as laminate C. A laminate B was prepared in the same manner as in Example 20, and a polyethyleneimine-based anchor coating agent was applied to the milk carton base paper surface of the laminate B at a rate of 0.1 g / m 2 Onto the anchor coat layer, adhesive resin C was extruded to a thickness of 20 μm using an extruder, and the layer was laminated to the vapor-deposited film surface of laminate C via adhesive resin C. In this way, a laminate of Example 21 was obtained in which the first layer, anchor coat layer, gas barrier resin layer, adhesive resin layer, and second layer were laminated in this order. The first layer in Example 21 was a laminate of a low-density polyethylene layer, anchor coat layer, milk carton base paper, anchor coat layer, adhesive layer, metal foil, dry laminate layer, and polyethylene terephthalate film laminated in this order.

[0088] [Example 22] A laminate of Example 22 was obtained in the same manner as in Example 20, except that the thickness of the gas barrier resin layer was adjusted to 5 μm.

[0089] [Example 23] A laminate of Example 23 was obtained in the same manner as in Example 20, except that the thickness of the gas barrier resin layer was adjusted to 15 μm.

[0090] [Example 24] A laminate of Example 24 was obtained in the same manner as in Example 20, except that gas barrier resin B was used instead of gas barrier resin A as the gas barrier resin.

[0091] [Example 25] A laminate of Example 25 was obtained in the same manner as in Example 20, except that gas barrier resin C was used instead of gas barrier resin A as the gas barrier resin.

[0092] [Example 26] A laminate of Example 26 was obtained in the same manner as in Example 20, except that gas barrier resin D was used instead of gas barrier resin A as the gas barrier resin.

[0093] [Example 27] A laminate of Example 27 was obtained in the same manner as in Example 20, except that adhesive resin B was used instead of adhesive resin A as the adhesive resin.

[0094] [Comparative Example 1] A polyurethane anchor coating agent was applied at 0.4 g / m2 to one side of the biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd., thickness: 25 μm) which was the first layer. 2The coating was applied in a dry coating amount of 1000 μm to form an anchor coat layer. On the anchor coat layer, gas barrier resin A, adhesive resin D, and low density polyethylene A were co-extruded using a co-extruder, while a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 20 μm) was laminated as a second layer via the gas barrier resin A, adhesive resin D, and low density polyethylene A. At that time, the thickness of the gas barrier resin layer made of the gas barrier resin A was 10 μm, the thickness of the adhesive resin layer made of the adhesive resin D was 5 μm, and the thickness of the low density polyethylene layer made of the low density polyethylene A was 10 μm. In this manner, a laminate of Comparative Example 1 was obtained in which the first layer, anchor coat layer, gas barrier resin layer, adhesive resin layer, low-density polyethylene layer, and second layer were laminated in this order.

[0095] [Comparative Example 2] A urethane anchor coating agent was applied at 0.4 g / m2 to one side of the biaxially oriented polyethylene terephthalate film (product name: E5100, manufactured by Toyobo Co., Ltd., thickness: 25 μm) which was the first layer. 2 The coating was applied in a dry coating amount of 100 μm to form an anchor coat layer. On the anchor coat layer, low-density polyethylene A, adhesive resin D, gas barrier resin A, adhesive resin D, and low-density polyethylene A were co-extruded using a co-extruder, and the low-density polyethylene A, adhesive resin D, gas barrier resin A, adhesive resin D, and low-density polyethylene A were laminated to a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 20 μm) which was the second layer, via the low-density polyethylene A, adhesive resin D, gas barrier resin A, adhesive resin D, and low-density polyethylene A. At that time, the thickness of the gas barrier resin layer made of the gas barrier resin A was 10 μm, the thickness of each of the adhesive resin layers made of the adhesive resin D was 5 μm, and the thickness of each of the low-density polyethylene layers made of the low-density polyethylene A was 10 μm. In this way, a laminate of Comparative Example 2 was obtained, in which a first layer, an anchor coat layer, a low-density polyethylene layer, an adhesive resin layer, a gas barrier resin layer, an adhesive resin layer, a low-density polyethylene layer, and a second layer were laminated in that order.

[0096] [Comparative Example 3] A laminate of Comparative Example 3 was obtained in the same manner as in Example 12, except that adhesive resin D was used instead of adhesive resin A as the adhesive resin.

[0097] [Comparative Example 4] A first layer similar to that of Example 14 was prepared, and a urethane anchor coating agent was applied at 0.4 g / m2 to the milk carton base paper surface of the first layer. 2 An anchor coat layer was formed by applying a dry coating amount of 0.4 g / m2 of adhesive resin E onto the anchor coat layer. An extruder was used to extrude adhesive resin E to a thickness of 20 μm, while the adhesive resin E was sandwiched between the extruder and an ethylene-vinyl alcohol copolymer film (product name: ZEX101, manufactured by Tamapoly Co., Ltd., thickness: 50 μm). A urethane-based anchor coat agent was applied to the ethylene-vinyl alcohol copolymer film at a dry coating amount of 0.4 g / m2. 2 Onto the anchor coat layer, low-density polyethylene A was extruded using an extruder to a thickness of 40 μm to form a second layer. In this manner, a laminate of Comparative Example 4 was obtained in which the first layer, anchor coat layer, adhesive resin layer, ethylene-vinyl alcohol copolymer film, anchor coat layer, and second layer were laminated in this order.

[0098] [Comparative Example 5] A first layer similar to that of Example 14 was prepared, and a urethane anchor coating agent was applied at 0.4 g / m2 to the milk carton base paper surface of the first layer. 2 Onto the anchor coat layer, adhesive resin E was extruded to a thickness of 20 μm using an extruder, and the layer was laminated, via adhesive resin E, to the deposition surface of a polyethylene terephthalate film (product name: 1012, manufactured by Toray Film Processing Co., Ltd., thickness: 12 μm) on which a deposition film made of aluminum had been formed. A urethane-based anchor coat agent was applied at a dry coating amount of 0.4 g / m on the polyethylene terephthalate film. 2Onto the anchor coat layer, low-density polyethylene A was extruded to a thickness of 20 μm using an extruder, and a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 40 μm) was laminated as a second layer via the low-density polyethylene A. In this way, a laminate of Comparative Example 5 was obtained, in which a first layer, an anchor coat layer, an adhesive resin layer, a polyethylene terephthalate film having an aluminum vapor deposition film formed thereon, an anchor coat layer, a low-density polyethylene layer, and a second layer were laminated in that order.

[0099] [Comparative Example 6] Basis weight: 383g / m 2 A urethane anchor coating agent was applied to one side of the milk carton base paper at 0.4 g / m 2 The dry coating amount was 1000 μm to form an anchor coat layer. Low density polyethylene A was extruded onto the anchor coat layer with an extruder to a thickness of 25 μm. In this way, a first layer consisting of the milk carton base paper, the anchor coat layer, and the low density polyethylene layer was produced. The first layer of the milk carton base paper is coated with a urethane anchor coating agent at 0.4 g / m 2 An anchor coat layer was formed by applying a dry coating amount of 0.4 g / m2 of the urethane-based anchor coat agent onto the aluminum foil while extruding adhesive resin E to a thickness of 20 μm using an extruder. 2 Onto the anchor coat layer, low-density polyethylene A was extruded to a thickness of 20 μm using an extruder, and a polyethylene film (trade name: LL-XMTN, manufactured by Futamura Chemical Co., Ltd., thickness: 40 μm) was laminated as a second layer via the low-density polyethylene A. In this manner, a laminate of Comparative Example 6 was obtained in which the first layer, anchor coat layer, adhesive resin layer, aluminum foil, anchor coat layer, low-density polyethylene layer, and second layer were laminated in this order.

[0100] [Comparative Example 7] A laminate of Comparative Example 7 was obtained in the same manner as in Example 20, except that instead of co-extruding the gas barrier resin A and the adhesive resin A, low-density polyethylene B was extruded to a thickness of 20 μm.

[0101] [Comparative Example 8] A laminate of Comparative Example 8 was obtained in the same manner as in Example 21, except that instead of co-extruding the gas barrier resin A and the adhesive resin A, low-density polyethylene B was extruded to a thickness of 20 μm.

[0102] [Comparative Example 9] The laminate of Comparative Example 9 was obtained in the same manner as Comparative Example 7, except that a three-layer film (product name: Diamiron (registered trademark), manufactured by Mitsubishi Chemical Corporation, thickness: 120 μm) consisting of a layer of polyethylene, a layer of ethylene-vinyl alcohol copolymer, and a layer of polyethylene laminated in that order was used instead of a polyethylene film (product name: M2005, manufactured by Aicello Co., Ltd., thickness: 40 μm) as the second layer.

[0103] The layer structures of the laminates of Examples 1 to 27 and Comparative Examples 1 to 9 are shown in Tables 1 and 2. Note that in Tables 1 and 2, layers between the first layer and the barrier layer are omitted.

[0104] [Measurement of the content of groups derived from maleic anhydride in the adhesive resin layer] A Ge prism was pressed against the adhesive resins A to E, and the infrared absorption spectrum was measured under the following measurement conditions using a Fourier transform infrared spectrometer (product name: Nicolet 6700, manufactured by Thermo Scientific). -1 The appearance of a peak of the group derived from maleic anhydride was confirmed, and the content of the group derived from maleic anhydride was calculated from the peak absorption intensity. The measurement results are shown in Table 2. For adhesive resin E, the wave number is about 1700 cm -1 Since no peak for groups derived from maleic anhydride appeared in this analysis, the content of groups derived from maleic anhydride was determined to be 0.00% by mass. (Measurement conditions) Incident angle: 45 degrees Resolution: 4cm -1 Measurement wave number range: 700~4000cm -1 Number of times accumulated: 64

[0105] [Evaluation of processability of laminates] In the process of producing the laminates of Examples 1 to 27 and Comparative Examples 1 to 9, the state of adhesion between the extruded adhesive resin and the metal chill roll or rubber nip roll was visually confirmed. The evaluation criteria were as follows. The results are shown in Table 3. (Evaluation Criteria) A: The adhesive resin did not adhere to either the metal chill roll or the rubber nip roll. B: The adhesive resin adhered to the metal chill roll or rubber nip roll.

[0106] [Evaluation of suitability for processing into liquid paper containers] The laminates of Examples 14 to 27 and Comparative Examples 4 to 9 were scored and punched with a punching machine to produce blank sheets. These blank sheets were then side-sealed with a frame sealing machine to produce sleeves, and 500 mL liquid paper containers with sides of 70 mm and height of 135 mm were produced with a hot air type filling and molding machine. In the process of manufacturing the liquid-cartons, the suitability for processing into liquid-cartons was evaluated according to the following evaluation criteria. The results are shown in Table 3. (Evaluation Criteria) A: The laminate folded at the punched area, and the top remained closed after the liquid paper container was made, so it was possible to process it into the desired liquid paper container. B: The laminate was bent in areas other than the punched areas, or the top of the liquid paper container opened up on its own after it was made, so it was not possible to process it into the desired liquid paper container.

[0107] [Appearance evaluation] The appearance of the laminates of Examples 1 to 13 and Comparative Examples 1 to 3 was visually confirmed. The evaluation criteria were as follows. The results are shown in Table 3. (Evaluation Criteria) A: No spots were observed on the laminate. B: Spots were observed in the laminate.

[0108] [Oxygen permeability measurement] The laminates of Examples 1 to 27 and Comparative Examples 1 to 9 were set so that the oxygen supply side was the first layer of the laminate using an oxygen transmission rate measuring device (model name: OX-TRAN 2 / 21, manufactured by MOCON Co., Ltd.), and the oxygen transmission rate (unit: cc / m) was measured in accordance with JIS K 7126-2:2006 under an environment of a temperature of 23°C and a relative humidity of 60%. 2 The lower the oxygen permeability, the better the gas barrier properties of the laminate. The measurement results are shown in Table 3.

[0109] [Comprehensive evaluation of the amount of resin used in the barrier layer and gas barrier properties] Using the thickness and oxygen permeability of the barrier layer in the laminate of Comparative Example 1 as the standards, the amount of resin used in the barrier layer and the gas barrier properties were comprehensively evaluated for the laminates of Examples 1 to 27 and Comparative Examples 2 to 9. The evaluation criteria were as follows. The results are shown in Table 3. A: The thickness of the barrier layer is 25 μm or less, and the amount of resin used in the barrier layer is small. B: Although the thickness of the barrier layer exceeds 25 μm, the oxygen permeability is smaller than that of the laminate of Comparative Example 1, and the large amount of resin used in the barrier layer contributes to improved gas barrier properties. C: The thickness of the barrier layer exceeds 25 μm, and the oxygen permeability is equal to or higher than that of the laminate of Comparative Example 1. The large amount of resin used in the barrier layer does not contribute to improving the gas barrier properties.

[0110] [Evaluation of suitability for contents resistance] Using the laminates of Examples 1 to 6, 8 to 11, and 13 and Comparative Examples 1 and 2 as the wall and bottom films, standing pouches with external dimensions of 170 mm height x 130 mm width, 40 mm height of the bottom fold-in part, and 5 mm seal width as shown in Fig. 3 were produced. The bottom was heat sealed with a boat-bottom seal pattern. The standing pouch was filled with 200 cc of an acidic solution (product name: Good Sense, manufactured by C.B.S. Co., Ltd., deodorant containing organic acid, pH: 3.5) as the content, and heat-sealed to seal. The filled standing pouch was stored for 6 weeks in an environment of a temperature of 40°C and a relative humidity of 90%RH. The state of the laminate after storage was visually confirmed, and the suitability for resistance to the content was evaluated according to the following evaluation criteria. The same storage tests were also conducted when the contents were replaced with an alkaline solution (product name: Laundrysh Pro, manufactured by C.B.S. Co., Ltd., laundry detergent containing 2-aminoethanol, pH: 10.4), PGMEA (propylene glycol monomethyl ether acetate), cyclohexane, ethyl acetate, and 99.5% ethanol, and the suitability for resistance to the contents was evaluated. For the laminates of Examples 14 to 27 and Comparative Examples 4 to 9, the suitability for resistance to contents was evaluated in the same manner as for the laminates of Examples 1 to 6, 8 to 11, and 13, and Comparative Examples 1 and 2, except that after evaluating the suitability for processing into liquid paper containers, each liquid paper container was filled with each content and a storage test was conducted. The results are shown in Table 3. (Evaluation Criteria) A: No delamination occurred in the laminate. B: Delamination occurred in the laminate.

[0111] [Table 1]

[0112] [Table 2]

[0113] [Table 3]

[0114] As is clear from Tables 1 to 3 above, the laminates of Examples 1 to 3 and 5 to 13 each had a barrier layer consisting of two layers, and thus the thickness of the barrier layer could be made smaller than that of the laminates of Comparative Examples 1 and 2 each consisting of three or five layers, allowing the amount of resin used to be reduced and allowing excellent gas barrier properties to be exhibited. Moreover, the laminate of Example 4, although consisting of only two layers, was able to exhibit even better gas barrier properties by deliberately increasing the thickness of the barrier layer. On the other hand, the laminate of Comparative Example 3 had a two-layer barrier layer, but the adhesive resin layer adhered to the metal chill roll or rubber nip roll during the production of the laminate, making it difficult to process.

[0115] As is clear from Table 3 above, the laminates of Examples 1 to 6, 8 to 11, and 13 to 27 did not undergo delamination even when various contents were stored, and had excellent suitability for content resistance. Furthermore, the laminates of Examples 14 to 27 could be processed into the desired paper containers for liquids, and had excellent suitability for processing into paper containers for liquids. [Explanation of symbols]

[0116] 10 Laminate 11 First layer 12 Barrier layer 13 Second layer 14 Gas barrier resin layer 15 Adhesive resin layer 30 Standing Pouch 31 Side sheet 32 Bottom sheet 41 Pillow Bag 42 Three-sided seal bag 43 Four-sided sealed bag 60 Liquid paper containers 61 Torso 62 Bottom 63 Top 63a Inclined plate 64 Folding section 65 Glue 66 Spout stopper 67 Straw Hole 70 Paper Cups 71 Flange 72 Torso 73 Bottom 74 Exterior body 75 Convex 76 Gap

Claims

1. A laminate comprising at least a first layer and a barrier layer, the barrier layer is a co-extruded layer of two layers, a gas barrier resin layer and an adhesive resin layer, the gas barrier resin layer is located between the first layer and the adhesive resin layer, the gas barrier resin layer contains an ethylene-vinyl alcohol copolymer, the adhesive resin layer is made of a resin composition containing an unmodified polyolefin and a maleic anhydride-modified polyolefin, The content of the unmodified polyolefin in the adhesive resin layer is 10% by mass or more and 80% by mass or less, The thickness of the adhesive resin layer is 3 μm or more and 20 μm or less.

2. The laminate according to claim 1 , wherein the content of groups derived from maleic anhydride in the adhesive resin layer is from 0.18% by mass to 0.25% by mass.

3. The laminate according to claim 1 or 2, wherein the resin composition has a melt flow rate of 2 g / 10 min or more and 13 g / 10 min or less.

4. The laminate according to claim 1 or 2, wherein the gas barrier resin layer has a thickness of 3 μm or more and 20 μm or less.

5. 3. The laminate according to claim 1, wherein the ethylene-vinyl alcohol copolymer has a content of structural units derived from ethylene of 20 mol % or more and 60 mol % or less.

6. 3. The laminate according to claim 1, wherein the ethylene-vinyl alcohol copolymer has a melt flow rate of 0.1 g / 10 min or more and 15 g / 10 min or less.

7. The laminate according to claim 1 or 2, wherein the barrier layer has a thickness of 10 μm or more and 30 μm or less.

8. The laminate according to claim 1 or 2, further comprising a second layer on the adhesive resin layer.

9. The laminate of claim 8 , wherein the second layer is a sealant film.

10. The laminate of claim 1 or 2, wherein the first layer comprises paper.

11. The oxygen permeability measured in accordance with JIS K 7126-2:2006 under an environment of 23°C temperature and 60% relative humidity is 10 cc / m 2 3. The laminate according to claim 1 or 2, wherein the thermal expansion coefficient is 0.05-0.55-day-atm or less.

12. A packaging container comprising the laminate according to claim 1 or 2.

13. The packaging container according to claim 12, which is a liquid paper container.

Citation Information

Patent Citations

  • Gas barrier packing material and its manufacture

    JP1995304139A

  • Laminate and method of manufacturing the same

    JP2012076305A

  • Paper container for liquid

    JP2013144556A